Psychological well-being of future specialists in the integrated educational environment and the factors of its formation - Serdiuk, Liudmyla (Social Welfare: Interdisciplinary Approach, 2011)
This paper deals with the factors affecting the psychological well-being of the person; the intensity of indexes of psychological well-being of personalities of both students with disabilities and healthy students in integrated groups has been analyzed: self-relationship, self-realization, and orientations of life-sense, interrelation of the past, present and future in the structure of psychological time of personality life have been discussed. The students with disabilities have more expressed demand in support and positive attitude to them. The reliable differences of a number of indexes of self-realization have been found, such as spontaneity (p<0,001), competency in time, value orientations, flexibility of behaviour, sensibility to oneself, self-esteem, self-understanding (p<0,05). The differences of life-sense orientations of students with disabilities are more expressed in such categories: orientation to process (p<0,001), locus of control of Self (p<0,001), and persistence in gaining the goal (p<0,05). Indexes of psychological time of personality life are expressed in the estimation of the expected span of life. Only 40 percent of students with disabilities have adequate psychological and chronicle ages but 27 per cent have overestimated and 33 per cent underestimated indexes. The great significance of social environment is shown in the process of adaptation and integration in educational environment.